Short Communication: Antibacterial activity of certain Saudi Arabian medicinal plants used in folk medicine against different groups of bacteria - ABDULLAH A. AL-GHANAYEM; SANAD M. AL SOBEAI; MOHAMMED S. ALHUSSAINI; BABU JOSEPH; ABDULMONEIM MOHAMMAD SAADABI (Smujo International, 2017)
Al-Ghanayem AA, Al Sobeai SM, Alhussaini MS, Joseph B, Saadabi AM. 2017. Antibacterial activity of certain Saudi Arabian medicinal plants used in folk medicine against different groups of bacteria. Nusantara Bioscience 9: 392-395. Medicinal plants from Saudi Arabia has been used in folk medicine for treatment of many diseases. The present research is on medicinal plants, which are locally available such as Acacia ehrenbergiana (Arabic: Salam) (Fabaceae), Calotropis procera (Arabic: Ausher) (Apocynaceae), Haloxylon salicornicum (Arabic: Rimth) (Amaranthaceae), Panicum turgidum (Arabic: Thuman) (Poaceae), Tamarix arabica (Arabic: Athal) (Tamaricaceae), Rhazya stricta (Arabic: Harmal) (Apocynaceae) Rumex vesicarius (Arabic: Humeid) (Polygonaceae) for antimicrobial activity by agar well diffusion method. Minimum Inhibitory Concentration (MIC) has been determined by broth micro dilution method. A. ehrenbergiana was active against Klebsiella pneumoniae. R. vesicarius and T. arabica showed antibacterial activity against Proteus vulgaris. C. procera showed a moderate inhibitory activity against the bacterial pathogens tested. H. salicornicum extract was more effective towards Gram-positive bacteria. However, other extracts such as P. turgidum and R. stricta were less active against both Gram-positive and negative bacteria tested. The results will be helpful in discovering new phytochemical components with antibacterial activity that can be used against multidrug-resistant bacterial strains.